Kualitas Pelayanan Transportasi Umum PERUM DAMRI Kalimantan Barat - Muhammad Rachimoellah; Dwi Haryono (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2021)
Cities in Indonesia are developing rapidly, as happened in West Kalimantan Province, where the population growth is getting faster every year, with the increasing population in West Kalimantan Province, the need for transportation will also increase. This study aims to determine and analyze the factors that cause the quality of transportation services at Perum Damri in West Kalimantan to be less than optimal. This research uses a qualitative approach, data collection is done by interviewing, observation and documentation techniques. The results of this study indicate that there are several factors that cause the quality of service at Perum Damri in West Kalimantan to be less than optimal, of the six factors, namely awareness, rules, organization, income, abilities and skills, and service facilities, there are three factors that cause service quality. Perum Damri's transportation in West Kalimantan is less than optimal, namely: awareness factors, regulatory factors, facilities and infrastructure factors., while organizational factors, abilities and skills and income are running optimally at PERUM DAMRI West Kalimantan. In this study, new things were also found, namely the guarantee of time certainty in which the community as service users was still a little disappointed with the delay in the arrival schedule of the Damri bus because there was still a delay in travel time even though the intensity was very low. It is hoped that Damri will pay more attention to bus arrival times by making various predictions and anticipations so that the guarantee of service time can be maintained.